Information quality in design process documentation of quality management systems. Issue 4 (August 2016) - Grudzień, Łukasz; Hamrol, Adam
Highlights: Information attributes for evaluating quality of process information have been established. A methodology of evaluating quality of process information is proposed. When designing the process documents, the information requirements of the process executor need to be taken into consideration. There exists a relation between attributes of process information and the type of process realized. Abstract: Information is the main constituent of documents that make up a quality management system. The main function of information found in process documents is to provide knowledge regarding how to executing a process and to standardize this process by providing a specific path of execution. However, it is not easy to determine a standard level of quality of process information optimal from the viewpoint of the owner and the process executor. Since there is no universal standard that would allow evaluation of the quality of process information, the purpose of the presented studies was to solve the aforementioned problems and to provide practical solutions for document makers to design proper process descriptions. To achieve the main purpose, a methodology for examination of influence characteristics of processes on information requirements of users of process documents was created. The paper presents findings carried out in processes at enterprises and is aimed at finding relation between attributes describing information and characteristics of processes. The paper proposes a set of guidelines developed by the authors for selection of appropriate document characteristics. These guidelines are based on findings collected from the conducted research.